Coal Combustion Byproducts and Environmental Issues - Sajwan, Kenneth S.; Twardowska, Irena; Punshon, Tracy; Alva, Ashok K. (Springer New York : Imprint: Springer, 2006)
Coal Combustion Byproducts and Environmental Issues addresses the major implications and critical issues surrounding coal combustion products and their impact upon the environment. It provides essential information for scientists conducting research on coal and coal combustion products, but also serves as a valuable reference for a wide variety of researchers and other professionals in the energy industry and in the fields of public health, engineering, and environmental sciences. The ultimate goal of this volume is to benefit both our economy and our environment as humanity enters the second half of the fossil fuel era.